Proton-coupled sugar transport in the prototypical major facilitator superfamily protein XylE - Wisedchaisri, Goragot (Nature Pub. Group, 2014)
The major facilitator superfamily (MFS) is the largest collection of structurally related membrane proteins that transport a wide array of substrates. The proton-coupled sugar transporter XylE is the first member of the MFS that has been structurally characterized in multiple transporting conformations, including both the outward and inward-facing states. Here we report the crystal structure of XylE in a new inward-facing open conformation, allowing us to visualize the rocker-switch movement of the N-domain against the C-domain during the transport cycle. Using molecular dynamics simulation, and functional transport assays, we describe the movement of XylE that facilitates sugar translocation across a lipid membrane and identify the likely candidate proton-coupling residues as the conserved Asp27 and Arg133. This study addresses the structural basis for proton-coupled substrate transport and release mechanism for the sugar porter family of proteins.